Carbon dioxide and methane fluxes from mounds of African fungus-growing termites - Räsänen, Matti; Vesala, Risto; Rönnholm, Petri; Arppe, Laura; Manninen, Petra; Jylhä, Markus; Rikkinen, Jouko; Pellikka, Petri; Rinne, Janne (Copernicus GmbH, 2023)
Termites play an essential role in decomposing dead plant material in tropical ecosystems and are thus major sources of gaseous C emissions in many environments. In African savannas, fungus-growing termites are among the ecologically most influential termite species. We studied the gas exchange from mounds of two closely related fungus-growing species (Macrotermes subhyalinus and M. michaelseni, respectively) in two habitats representing different vegetation types (grassland, bushland) together with soil fluxes around the mounds. The fluxes from active termite mounds varied from 120 to 2100 mg CO2–C m−2 h−1 for carbon dioxide (CO2) and from 0.06 to 3.7 mg CH4–C m−2 h−1 for methane (CH4) fluxes. Mound CO2 fluxes varied seasonally with a 64 % decrease and 41 % increase in the fluxes from the dry to wet season at the grassland and bushland sites, respectively. During the wet season, the CO2 fluxes were significantly correlated with termite mound volume. The diurnal measurements from two M. michaelseni mounds suggest that the gas fluxes peak during the daytime, possibly reflecting changes in mound internal air circulation. Soil fluxes of both CO2 and CH4 were enhanced at up to 2 m distance from the mounds compared to the local soil respiration, indicating that, in addition to mound ventilation structures, a small proportion of the metabolic gases produced also leave the nest via surrounding soils.